Metaforični potencial kolokacij: primer samostalnika prilika - Stojić, Aneta; Matešić, Mihaela (Slavia Centralis, 2024)
This paper examines the nature of collocational bonds within lexical collocations where at least one component is metaphorical. Using the Croatian web corpus hrWaC and the SketchEngine (WordSketch function), we systematically investigate the most typical collocations and word combinations involving the polysemous abstract noun ‘prilika’. Based on the analysis of both morphosyntactic and semantic processes within the collocational bond, we conclude that these processes contribute to the cohesion between the collocate and base, thereby strengthening the bonding of lexemes into a lexical collocation.